On adjectival connotations - Kjellmer, Gőran (Adam Mickiewicz University, 2009)
Connotations are elusive semantic elements. Although they are often specific to individual speakers, many of them are sufficiently general to serve as general communicative elements. The paper suggests a device by means of which adjectival connotations, whether of the individual or the general type, can be pinpointed. The device is simply the sequence “ADJ1 but not ADJ2”, where ADJ2 is seen to enrich the connotational semantics of ADJ1. Thus for example the use of a phrase like desirable but not essential may indicate that desirable normally contains an element of essential, though perhaps not in the situation where it is used. It is pointed out that ADJ2 often represents an intensification of the semantic content of ADJ1.